1997
DOI: 10.1152/jn.1997.77.3.1155
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the Spinal Network Associated With Generation of Hindlimb Locomotion in the Neonatal Rat and Organization of Its Transverse Coupling System

Abstract: The segmental organization of the hindlimb locomotor pattern generators and the coordination of rhythmic motor activity were studied in isolated spinal cords of the neonatal rat. All lumbar segments and many thoracic and sacral segments of the cord exhibited an alternating left-right rhythm in the presence of serotonin (5-HT) and N-methyl-D-aspartate (NDMA). Other thoracic segments exhibited a synchronized left-right rhythm or an irregular bursting activity. Transection of the cord at the thoracolumbar or lumb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
185
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 214 publications
(203 citation statements)
references
References 45 publications
17
185
0
1
Order By: Relevance
“…To better assess the significance of the observed correlation coefficient, both the SE (dashed line in all correlations) and the fourfold SE (solid line in all correlations) were calculated and shown in the figures (cf. Kremer and Lev-Tov, 1997;Cangiano and Grillner, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To better assess the significance of the observed correlation coefficient, both the SE (dashed line in all correlations) and the fourfold SE (solid line in all correlations) were calculated and shown in the figures (cf. Kremer and Lev-Tov, 1997;Cangiano and Grillner, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Cross-correlations were computed for every section and, from the entire set, an average and SE were obtained. Membrane potential oscillations were considered significantly correlated to ventral root bursting if the central peak of the average cross-correlation exceeded four times the SE (Kremer and Lev-Tov, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…Spinal cords (T6-Co3) were isolated from P1-P3 isoflurane-anesthetized male or female rats (Lev-Tov and Delvolvé, 2000;Lev-Tov et al, 2000;Delvolvé et al, 2001;Blivis et al, 2007). Preparations were transferred to a recording chamber and superfused continuously with an oxygenated artificial CSF (Kremer and Lev-Tov, 1997;Lev-Tov et al, 2000;Delvolvé et al, 2001;Blivis et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…10,32 Several other lines of evidence indicate that in the neonatal rat, the network of interconnected spinal interneurons, which are capable of generating locomotor-like activity, located in the rostral lumbar segments shows greater capacity for rhythmicity than that in other segments. 13,14,28 Noteworthy, Gabbay and Lev-Tov 33 showed that in early developmental period not only rostral lumbar but also sacrococcygeal segments responded differently to NA than to caudal lumbar segments. The bath-applied NA induced fast rhythms, which mimicked locomotor activity of the spinal cord in rostro-lumbar and sacrococcygeal, but not in caudal lumbar segments.…”
Section: Discussionmentioning
confidence: 99%
“…The data indicating that the network of interconnected spinal interneurons located in rostral lumbar segments of the rat may play prominent role in the control of spinally distributed locomotor network [10][11][12][13][14] prompted us to verify whether the neurochemical activity in rostral versus caudal lumbar segments is similarly modulated by long-term, moderate locomotor exercise.…”
Section: Introductionmentioning
confidence: 99%